10Be exposure dating of river terraces at the southern mountain front of the Dzungarian Alatau (SE Kazakhstan) reveals rate of thrust faulting over the past ~ 400 ka. Issue 1 (January 2014) - Cording, Anja; Hetzel, Ralf; Kober, Martin; Kley, Jonas
Abstract: The mountain belts of the Dzungarian Alatau (SE Kazakhstan) and the Tien Shan are part of the actively deforming India–Asia collision zone but how the strain is partitioned on individual faults remains poorly known. Here we use terrace mapping, topographic profiling, and 10 Be exposure dating to constrain the slip rate of the 160-km-long Usek thrust fault, which defines the southern front of the Dzungarian Alatau. In the eastern part of the fault, where the Usek River has formed five terraces (T1 –T5 ), the Usek thrust fault has vertically displaced terrace T4 by 132 ± 10 m. At two sites on T4, exposure dating of boulders, amalgamated quartz pebbles, and sand from a depth profile yielded 10 Be ages of 366 ± 60 ka and 360 + 77 /− 48 ka (both calculated for an erosion rate of 0.5 mm/ka). Combined with the vertical offset and a 45–70° dip of the Usek fault, these age constraints result in vertical and horizontal slip rates of ~ 0.4 and ~ 0.25 mm/a, respectively. These rates are below the current resolution of GPS measurements and highlight the importance of determining slip rates for individual faults by dating deformed landforms to resolve the pattern of strain distribution across intracontinental mountain belts.